The Application of Organic Plant Media Composition on Indian Mustard Crops (Brassica Juncea L) in Polybag - Augustien, Nora; Indah, Pawana Nur; Arika , Purnawati; Irsyad, Irsyad; Suhardjono , Hadi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2017)
Indian mustard plants are the main vegetable crops consumed by urban communities. The need for this vegetable increases along with the increase in culinary tourism in each region and the government's appeal on sustainable food home. One effort made to meet the needs of vegetable mustard in urban areas can be cultivated using polybags. The main problem of vegetable cultivation on polybags is the availability of soil media. To overcome the limitations of soil media it is attempted to substitute it with organic litter enriched with MOL (local microorganisms). The purpose of research is to find the right combination of planting media for mustard plants. The results showed that the composition of K7 = soil: compost: litter of hay: litter of maize (2: 1: 1: 1) best on plant length, number of leaves, length of root leaves and number of roots while the wet weight of mustard plant (g) K7 = soil: compost: litter of maize: litter of corn (2: 1: 1: 1) and K8 = soil: compost: litter of maize: litter of maize: cocopeat (2: 1: 1: 1: 1) or soil: compost + urea. Increased weights of wet mustard by 63% compared to soil media and 20% compared to soil composition: compost + urea. Organic straw in the form of straw: litter of corn stalk: cocopeat enriched with MOL are able to become ready-made planting media on the cultivation of indian mustard plants in polybags.